2004
DOI: 10.1007/s00216-004-2817-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification and quantification of gossypol in cotton by using packed micro-tips columns in combination with HPLC

Abstract: Self-packed micro-tip columns containing a C18-bonded silica stationary phase, based on the same principles as solid-phase extraction methods, were used to obtain gossypol and related sesquiterpenoid aldehyde-enriched fractions. The enriched metabolite fractions were then analyzed by optimized high-performance liquid chromatography (HPLC) with a C18 column (4.6 mm x 25 cm) eluted with the binary mobile phase acetonitrile-0.1% aqueous TFA solution (80:20). This method has proven to be highly reproducible. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
2
3
0
1
Order By: Relevance
“…The choice of the proper solvents; CHCL3 for gossypol, and EtOAc for gossypin may depend on the solubility of the phenolic nature of these components [33]. These findings are in agreement with Meyer et al (2004) [34] who indicated that the methanol extract is the best solvent to be used for the quantitative HPLC of these phenolics. The industrial waste showed to contain only gossypin and free from gossypol because this waste contain some seed as appear in (fig 1c) that findings are agreements with European Food Safety Authority [35]…”
Section: Quantitative Estimation Of Gossypin and Gossypol In Cotton W...supporting
confidence: 78%
“…The choice of the proper solvents; CHCL3 for gossypol, and EtOAc for gossypin may depend on the solubility of the phenolic nature of these components [33]. These findings are in agreement with Meyer et al (2004) [34] who indicated that the methanol extract is the best solvent to be used for the quantitative HPLC of these phenolics. The industrial waste showed to contain only gossypin and free from gossypol because this waste contain some seed as appear in (fig 1c) that findings are agreements with European Food Safety Authority [35]…”
Section: Quantitative Estimation Of Gossypin and Gossypol In Cotton W...supporting
confidence: 78%
“…The gossypol content in the seed and other organs is closely related to the overall glandulosity and the genotype [12,64,65]. The total gossypol content of seeds of different genotypes varied from as low as 0.2 ± 0.05 mg/g DW to as high as 64 ± 1.5 mg/g DW [62,66]. One acre of cotton crop is estimated to yield 150 kg dry root bark, from which about 1.4 kg of pure gossypol can be recovered [67].…”
Section: Discussionmentioning
confidence: 98%
“…The following elution gradient was applied: 0 min: 60 per cent B (40% A); 2 min: 60 per cent B; 20 min: 70 per cent B; 21 min: 100 per cent B; 25 min: 100 per cent B; 26 min: 60 per cent B; 35 min: 60 per cent B. Eluent A consisted of MilliQ-water, and eluent B consisted of acetonitrile. Eluent A was acidified with 0.1 per cent trifluoroacetic acid (greater than or equal to 99%, Riedel de Haën, Seelze Germany) to pH ¼ 2.5 (based on [22]). The flow rate of the mobile phase was 0.125 ml min -1 , and a 10 ml sample was injected.…”
Section: (C) Terpenoid Quantificationmentioning
confidence: 99%